MARKETING STRATEGY ANALYSIS OF SHARIA MICRO FINANCIAL INSTITUTIONS IN MURABAHAH FINANCING PRODUCTS - Muhammad Tho'in (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research was conducted with the aim of knowing various kinds of promotion strategies for Sharia micro-Sharia financial institutions with the object of research, namely BMT Samara in promoting financing products and identifying strategies to obtain and increase the number of members (customers). The product that is the focus of this research is the murabahah financing product. This research is in the form of field research with descriptive qualitative analytic methods. The research data comes from interviews, observations, and questionnaires. The results showed that BMT Samara implemented a promotional mix strategy, including: 1). Advertising through radio broadcasts, talk shows and banner media; 2). Sales promotion of its financing products; 3). Even and experiences through recitation activities, breaking fast with orphans in the month of Ramadan, and distributing gifts on Idul Fitri; 4). Public relations and publicity through the slaughter of sacrificial animals during Idul Adha; 5). Personal selling through the activity of reducing employees to the community accompanied by pamphlets; 6). Direct marketing through the internet, namely the website; 7). Interactive online marketing is carried out with social media accounts for Facebook, Instagram, and WhatsApp group; 8). Word of mouth marketing. The most dominant promotional strategy in attracting new members or customers is events and experiences and public relations and publicity. The implication of conducting this research is that a variety of promotional strategies are needed and continue to make marketing innovations for Sharia microfinance institutions in order to increase the number of members (customers) and maintain the existence of their superior products in order to be able to compete and develop in the midst of intense competition in the financial industry.